THE EFFECT OF HEALTH EDUCATION ON THE PREVENTION OF FLOUR ALBUS IN LHOKNGA PRISON, THE DISTRICT OF ACEH BESAR - Miftahul Jannah; Fitriani; Anita (Department of Midwifery, Health Polytechnic of Aceh, 2022)
Introduction: Flour albus is one of the most common reproductive health problems in women. Approximately 75% of women in the world suffer from flour albus at least once in their lifetime, and 45% of women experience vaginal discharge twice or more. Method: This study was quasi-experimental with a one-group pretest-posttest design, data were collected by questionnaires and was conducted on March 22, 2019. A total sampling technique was used in this study. Sampling was done using. Data analysis using Wilcoxon test. Result: The results showed that out of 27 respondents, 3.33% had negative attitudes before being given health education and 59.3% had positive attitudes after being given health education, and after statistical testing with the wilcoxon test, the p-value was 0.020 (p≤0.05). Conclusion: There was a significant impact of providing health education on the attitudes among female prisoners to prevent flour albus